Determinantes ambientais e estratégias de internacionalização: o caso da Companhia Siderurgica Nacional - Proença, Eduardo de Rezende (2006)
This research investigates the relationship between the determinants of internationalization process of a great Brazilian company and the strategies adopted for its insertion in the external market. The evolution of the internationalization process will be based in a case study in the National Steel Company (CSN). Specialists affirm that a company needs to increase its compromising and insertion in the international market to increase competitiveness. Exhibition into other markets make possible the learning and it presents opportunities and threats to the international company. However, in spite of the advantages of performance in other markets, the Brazilian companies act timidly at other markets. This incipient character provoked us to research the determinants and strategies of international insertion of CSN, a big one in Brazilian company that began internationalization process in the end of the seventies, with their first exports. The observation of the case CSN allows to notice the evolution of the process of internationalization of the company, characterized in two phases. The first, until half of the nineties, marked by the performance in the exterior through Tradings Companies, while second, starting from 1995, begins the compromising of resources into foreign markets. These strategies can be related with the determinants or incentives in the search for other markets. This dissertation discusses incentives as the saturation of the Brazilian internal market, the search of external markets to gain production scale, the compromising of resources in the exterior to overcome the customs barriers and to elevate the knowledge on the operation of the external markets, among other decisive. The objective of this research is to relate them with the strategies of performance in the exterior to show roads and incentives for other companies act in the exterior